Semen Quality of Infertile Men and Correlation with Demographic Characterictics - Iqbal, Muhammad; Karmia, Hudila Rifa; Alvarino, Alvarino (Andalas Obstetrics And Gynecology Journal, 2022)
Objective: To analyze semen quality of infertile men and its correlation with demographics characteristics.Methods: This was an analytic observational study with cross-sectional retrospective study design on 92 infertile men. The study began in May 2021 to December 2021 in the Obstetrics and Gynecology Clinics at BMC Hospital Padang.Results:The correlation between age and marital duration was positively correlated (r= 0,558), with a weak correlation and there is statistically significant relationship between age and marital duration. Age and sperm concentration was positively correlated (r=0.048), with a weak correlation. Marital duration and sperm concentration was positively correlated (r=0.052), with a weak correlation. The correlation between age and progressive motility and non-progressive motility percentage were positively correlated (r = 0.009 and 0.035),with a weak correlation. The correlation between age and progressive immotile sperm percentage were negatively correlated (r = - 0,030),with a weak correlation.Conclusion: There was a positive correlation between age and sperm concentration, and progressive and non progressive motility with a weak correlation. There was a positive correlation between age and marital duration with a strong correlation. There was negative correlation between and sperm immotility with a weak correlation.Keywords: Â male infertility, semen, age, marital duration